2019
DOI: 10.1162/jocn_a_01345
|View full text |Cite
|
Sign up to set email alerts
|

The Hippocampus Generalizes across Memories that Share Item and Context Information

Abstract: Episodic memory is known to rely on the hippocampus, but how the hippocampus organizes different episodes to permit their subsequent retrieval remains controversial. One major area of debate hinges on a discrepancy between two hypothesized roles of the hippocampus: differentiating between similar events to reduce interference and assigning similar representations to events that share overlapping items and contextual information. Here, we used multivariate analyses of activity patterns measured with fMRI to cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 57 publications
1
25
1
Order By: Relevance
“…Accordingly, we maintain that both source memory and pattern separation rely on complex hippocampal circuits rather than distinct regions. Indeed, a recent study by Libby et al (2018) found that patterns of hippocampal activity discriminated among similar items and similar contexts, but generalized across similar items-in-context, suggesting complex interactions. However, the dissociated signals elicited by source memory and pattern separation in the present study indicate that these processes may rely on distinct neural mechanisms that can be identified when the two processes are pitted against each other in an experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we maintain that both source memory and pattern separation rely on complex hippocampal circuits rather than distinct regions. Indeed, a recent study by Libby et al (2018) found that patterns of hippocampal activity discriminated among similar items and similar contexts, but generalized across similar items-in-context, suggesting complex interactions. However, the dissociated signals elicited by source memory and pattern separation in the present study indicate that these processes may rely on distinct neural mechanisms that can be identified when the two processes are pitted against each other in an experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…Beta images went through a second visual inspection to make sure all the deviant trials were excluded. This noise trial exclusion procedure is adopted from the previous pattern similarity studies in the lab (Libby, Reagh, Bouffard, Ragland, & Ranganath, 2019).…”
Section: Pattern Similarity Analysismentioning
confidence: 99%
“…Context-dependent memory with neutral valence -in contrast to contextual classical or operant conditioning [8]-is in humans often experimentally investigated via the combined presentation of items -like faces [9][10][11][12], everyday objects [11][12][13][14], or words [15,16]-and contexts -like scene pictures [9][10][11][12]15,16], words [14] or sounds [13]-in a computer task [17].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, the most widely used task to assess neutral context-dependent memory uses physical objects instead of virtual items. This task is commonly known as the object-incontext task (OIC) [18] and relies on the hippocampal system and associated cortical regions [1,19], comparable to human context-dependent memory [14,17,20]. In the OIC test the hippocampal system is needed to establish the link between the object's features and the contextual features; that is, without the hippocampal system an animal is able to remember the object in the sense of familiarity, but not remember the context in which it was encountered [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation